The Effect of Online QuizWhisser Game on Knowledge and Level of Fish Consumption in Overweight Adolescents in Surakarta - Euphrasia Pelletier Berek; Kusnandar; Sapja Anantanyu (International Journal of Science and Society, 2022)
Obesity is the accumulation of excessive fat which causes the overweight. Obesity or overweight in terms of health is a disease of malnutrition, as a result of food consumption that far exceeds its needs. To overcome it, knowledge needs to be increased as a precaution by conducting nutrition education. The sampling technique used is purposive sampling, followed by random sampling that is used to determine the sample. The respondents consist of 68 junior high school students in Surakarta City. First, the subjects are screened using a google form containing several questions regarding personal data. Then, the adolescents who had a z-score >1 SD were used as the research samples. The results of statistical tests after nutrition education in the control groups and the treatment group showed that there is a significant difference in nutritional knowledge (p = 0.000) while the results of statistical tests on fish consumption levels in the two groups showed that there is no difference and no significant effect was indicated by (p-value > 0.05). Conclusion: Nutrition talks and quizwhisser games about the importance of fish consumption affect the nutritional knowledge of overweight adolescents. However, they do not affect the level of fish consumption in overweight adolescents.